2019
DOI: 10.1021/acs.iecr.9b01831
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Polyhydroxyalkanoate Production from Combined Treatment of Organic Fraction of Municipal Solid Waste and Sewage Sludge

Abstract: Although the organic fraction of municipal solid waste (OFMSW) and sewage sludge (SS) originate from the same urban area and contain similar organic matter, they are collected separately and handled with different technologies. In this work, a combined treatment of OFMSW−SS mixture was investigated at pilot scale, by using a three-step mixed microbial culture (MMC) process in order to produce polyhydroxyalkanoate (PHA) as final high value biobased product. Biomass selection efficiency was quantified by PHAspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 34 publications
(100 reference statements)
7
79
1
Order By: Relevance
“…HRT), allowing the maintenance of good biogas yields and potentially improving the economic efficiency and viability of the AD process. Furthermore, the results showed that the average concentration of methane content (% v/v) in the biogas did not change significantly throughout the different experimental periods, with values in the range of 64% to 67% (v/v) and similar to those previously reported (Valentino et al, 2019). Overall, the cumulative biogas and biomethane yield obtained in this study were in line with results reported in literature for similar substrates and OLRs (Agyeman and Tao, 2014).…”
Section: Ofmsw Composition and Characteristicssupporting
confidence: 91%
“…HRT), allowing the maintenance of good biogas yields and potentially improving the economic efficiency and viability of the AD process. Furthermore, the results showed that the average concentration of methane content (% v/v) in the biogas did not change significantly throughout the different experimental periods, with values in the range of 64% to 67% (v/v) and similar to those previously reported (Valentino et al, 2019). Overall, the cumulative biogas and biomethane yield obtained in this study were in line with results reported in literature for similar substrates and OLRs (Agyeman and Tao, 2014).…”
Section: Ofmsw Composition and Characteristicssupporting
confidence: 91%
“…The Treviso pilot plant (TV) feedstock was a mixture of liquid slurry from squeezing the organic fraction of municipal solid waste (OFMSW) and biological sludge from urban wastewater treatment. The detailed process is given in Valentino et al [26]. Briefly, the main process steps were a first anaerobic fermentation reactor for PHA-precursor (volatile fatty acid, VFA) production, a second aerobic reactor (sequencing batch reactor, SBR) for biomass cultivation, and a third fed-batch aerobic reactor for PHA accumulation within cellular wall.…”
Section: Pha Production and Extractionmentioning
confidence: 99%
“…Industrial-scale PHA production is based mainly on pure-culture systems with refined feedstock and sterile cultivation conditions. Both features result in high-energy consumption, thereby strongly increasing production costs (Valentino et al, 2019). Consequently, PHA cannot be cost-competitive to conventional petroleum-based plastics.…”
Section: Polyhydroxyalkanoate Accumulation In Wastewater Treatment Plmentioning
confidence: 99%
“…An innovative approach has been proposed to combine PHA production with sludge minimization in municipal wastewater treatment. In the publications that make up this trend, both the impact of changing the approach to wastewater on the natural environment (Valentino et al, 2015 ) and the life cycle assessment (LCA) analysis of the production process (Morgan-Sagastume et al, 2016a ), as well as specific examples of biochemical (Yang et al, 2013 ; Inoue et al, 2016 ) and industrial processes (Pittmann and Steinmetz, 2014 ; Valentino et al, 2019 ) resulting in biopolymers, are presented. In the publications, an economic analysis of the process on the example of selected European countries is also carried out (Pittmann and Steinmetz, 2017 ).…”
Section: Trends Unveiledmentioning
confidence: 99%
See 1 more Smart Citation